1990
DOI: 10.1002/bjs.1800770405
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic gallstones

Abstract: The increasing detection of asymptomatic gallstones leads to difficult decisions for the surgeon and patient about whether the stones should be managed expectantly or surgically. This review examines the evidence currently available upon which such decisions must be based. Gallstones may present as biliary pain, acute cholecystitis, biliary obstruction or pancreatitis, but it is not clear who will develop symptoms and what are the commonest initial symptoms. Studies of the natural history of silent gallstones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
10

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 64 publications
2
73
0
10
Order By: Relevance
“…The incidence of asymptomatic patients with gallstones who became symptomatic was 10% to 18% over a five to 15 year follow-up period (20). The present study showed that 54% of 13 patients underwent cholecystectomy, indicating that gallstones that developed after esophagectomy should not be treated as they are in the general population.…”
Section: Discussionmentioning
confidence: 55%
“…The incidence of asymptomatic patients with gallstones who became symptomatic was 10% to 18% over a five to 15 year follow-up period (20). The present study showed that 54% of 13 patients underwent cholecystectomy, indicating that gallstones that developed after esophagectomy should not be treated as they are in the general population.…”
Section: Discussionmentioning
confidence: 55%
“…Most gallstones are asymptomatic (2,3), being incidentally detected on routine abdominal ultrasound (4). Approximately 90% of acute cholecystitis cases have gallstones associated with secondary bacterial infections and gallbladder inflammation (5-7); the remaining 10% of cases have what is termed acalculous cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…always endangers these patients. 4,6,7 Although literature advocates elective cholecystectomy after first episode of biliary pain (early management), still majority of the patients in developing countries like India neglect these symptoms. It might be due to poverty, illiteracy, scarcity of health facilities especially in rural areas, and low awareness levels about the disease.…”
Section: Introductionmentioning
confidence: 99%
“…always endangers these patients. 4,6,7 Although literature advocates elective cholecystectomy after first episode of biliary pain (early management), still majority of the ABSTRACT Background: Cholelithiasis is a commonly encountered entity by surgeons all over the globe. Its significantly higher incidence in certain regions of world like north India is a matter of concern.…”
mentioning
confidence: 99%